2013
DOI: 10.1155/2013/303902
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Preservesβ-Cell Mass and Function in Fructose-Induced Hyperinsulinemia through Modulating Pancreatic Akt/FoxO1 Activation

Abstract: Fructose-induced hyperinsulinemia is associated with insulin compensative secretion and predicts the onset of type 2 diabetes. In this study, we investigated the preservation of dietary flavonoid quercetin on pancreatic β-cell mass and function in fructose-treated rats and INS-1 β-cells. Quercetin was confirmed to reduce serum insulin and leptin levels and blockade islet hyperplasia in fructose-fed rats. It also prevented fructose-induced β-cell proliferation and insulin hypersecretion in INS-1 β-cells. High f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 53 publications
1
25
0
2
Order By: Relevance
“…Furthermore, fructose increased SOCS3 expression, decreased STAT3 phosphorylation, increased Pdx1 and insulin gene expression, and induced hyperinsulinemia both in rats and in INS-1 cells [19]. Quercetin treatment suppressed the increased SOCS3 level, elevated the reduced STAT3 level, and improved leptin signalling, thereby protecting beta-cell function under high-fructose conditions [19]. In accordance with the previous studies, in our study, over expression of SOCS3 inhibited STAT3 phosphorylation and then increased preproinsulin mRNA expression.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, fructose increased SOCS3 expression, decreased STAT3 phosphorylation, increased Pdx1 and insulin gene expression, and induced hyperinsulinemia both in rats and in INS-1 cells [19]. Quercetin treatment suppressed the increased SOCS3 level, elevated the reduced STAT3 level, and improved leptin signalling, thereby protecting beta-cell function under high-fructose conditions [19]. In accordance with the previous studies, in our study, over expression of SOCS3 inhibited STAT3 phosphorylation and then increased preproinsulin mRNA expression.…”
Section: Discussionsupporting
confidence: 91%
“…However, Seufert et al found that leptin increases the binding of STAT5b to the upstream sequences of the rat preproinsulin 1 promoter and inhibits insulin biosynthesis via transcriptional repression [18]. Furthermore, fructose increased SOCS3 expression, decreased STAT3 phosphorylation, increased Pdx1 and insulin gene expression, and induced hyperinsulinemia both in rats and in INS-1 cells [19]. Quercetin treatment suppressed the increased SOCS3 level, elevated the reduced STAT3 level, and improved leptin signalling, thereby protecting beta-cell function under high-fructose conditions [19].…”
Section: Discussionmentioning
confidence: 99%
“…STZ is a natural compound that can induce DN through selectively destroying islet β cells of animals, because DN is usually associated with reduced viability and dysfunction of pancreatic β cells 23 . The rat DN model induced by STZ increased FBG and proteinuria in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of Akt through the mTOR–PI3K pathway both counteracts MAPK signaling and activates CREB ( 59 ), at the same time directly inactivating FoxO1 ( 55 ). Quercetin treatment activates Akt in multiple cell types, leading to decreased activity of FoxO1 in pancreatic islets ( 60 ), and ameliorating the inflammatory response of adipocytes to TNFα ( 61 ). Akt activation has also been shown to correlate with suppression of FoxO1 in HEK293 cells ( 62 ).…”
Section: Competitive Circuitry Governing Innate Programing Of Leukocymentioning
confidence: 99%